The Impact of Pharmacist Mediated Education on Knowledge, Attitude, and Practices of Rural Adolescent Girls Towards Menstrual Hygiene: Nil - MEGHA, THAKUR; ADEPU, RAMESH; AKHILA, GUNDU; SANDHYA, CHERIPALLY; D, MOUNIKA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
A prospective interventional study is conducted to study the influence of pharmacist-provided education on knowledge, attitude, and practices (KAP) of school-going adolescent girls towards menstrual hygiene practices in rural Suryapet, Telangana. After obtaining permission from the school, adolescent girls meeting the study criteria were included in the study. A 13 item KAP questionnaire was designed, validated, and administered to girls. A structured education was given about menstrual hygiene management to them. Post-education, the KAP questionnaire was readministered and results were analyzed. A total of 206 students were enrolled in the study, and 90(43.0%) students were in the age group of 14. Knowledge about menstruation was 27.18% in pretest and it was 94.68% after posttest showing a significant (p < 0.01) improvement. After the education, the respondents have changed their opinion from “menstruation as a curse from God” (63.59%) to “as a natural process (95.63%). Mother was named as the main information source about menstruation, followed by teachers and friends. Post-education increased the attitude of maintaining regular genital hygiene from 86.40% to 96.60%. Proper discard of menstrual waste to refuse bin increased from 54.85% to 95.15% indicating the overall improvement in knowledge, attitude, and practice regarding menstrual hygiene among adolescent girls.